Regional Assets Management in the Management of Kinantan Wildlife and Culture Park (TMSBK) Bukittinggi City - Zhahrah Indah Pratiwi; Hendri Koeswara; Ria Ariany (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is motivated by the management of TMSBK assets carried out by the Tourism, Youth, and Sports Office of Bukittinggi City. The existence of asset management that has been carried out has an impact on the increase in PAD in the City of Bukittinggi in the tourism sector. The purpose of this study is to analyze asset management in the management of TMSBK in Bukittinggi City. This study uses the Theory of Five Stages of Asset Management Work proposed by Doli D. Siregar. The type of research used in this research is qualitative research with descriptive data presentation. Data collected through the process of observation, interviews and documentation. The selection of informants was done by purposive sampling technique. To test the validity of the data using source triangulation techniques. Based on the results of the study, it was found that the management of TMSBK assets had been carried out optimally. Among them is the recording of assets which is carried out through recording into the inventory book and recording into the SIMDA BMD application, as for the legal basis that is used as a reference in asset management, namely Permendagri Number 19 of 2016 concerning Guidelines for the Management of Regional Property, asset valuation carried out by PBMD which cooperate with the KPKNL in determining the value of assets for asset write-off and determining the rental value of the TMSBK kiosk. There is a revitalization of the TMSBK area in order to add value and function to these assets, as well as supervision and control carried out by the Inspectorate as the government's internal supervisory agency and the development of an asset management information system through the use of the SIMDA BMD application. Several stages that have not been carried out optimally are the internal recording carried out by the TMSBK sector and the need for a review of abandoned assets.